MicroRNA 665 Regulates Dentinogenesis through MicroRNA-Mediated Silencing and Epigenetic Mechanisms - Heair, Hannah M. (Mol Cell Biol, 2015)
Studies of proteins involved in microRNA (miRNA) processing, maturation, and silencing have indicated the importance of miRNAs in skeletogenesis, but the specific miRNAs involved in this process are incompletely defined. Here, we identified miRNA 665 (miR-665) as a potential repressor of odontoblast maturation. Studies with cultured cell lines and primary embryonic cells showed that miR-665 represses the expression of early and late odontoblast marker genes and stage-specific proteases involved in dentin maturation. Notably, miR-665 directly targeted Dlx3 mRNA and decreased Dlx3 expression. Furthermore, RNA-induced silencing complex (RISC) immunoprecipitation and biotin-labeled miR-665 pulldown studies identified Kat6a as another potential target of miR-665. KAT6A interacted physically and functionally with RUNX2, activating tissue-specific promoter activity and prompting odontoblast differentiation. Overexpression of miR-665 reduced the recruitment of KAT6A to Dspp and Dmp1 promoters and prevented KAT6A-induced chromatin remodeling, repressing gene transcription. Taken together, our results provide novel molecular evidence that miR-665 functions in an miRNA-epigenetic regulatory network to control dentinogenesis.